2018
DOI: 10.1097/ajp.0000000000000515
|View full text |Cite
|
Sign up to set email alerts
|

Combination Drug Therapy of Pioglitazone and D-cycloserine Attenuates Chronic Orofacial Neuropathic Pain and Anxiety by Improving Mitochondrial Function Following Trigeminal Nerve Injury

Abstract: The DCS/PIO combination uncoupled mitochondrial respiration in the TIC model to improve cortical mitochondrial dysfunction, as well as reduced nociceptive and anxiety behaviors present in mice with centralized chronic neuropathic nerve injury. Combining these drugs could be a beneficial treatment for patients with depression, anxiety, or other psychological conditions due to their chronic pain status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
1
17
0
1
Order By: Relevance
“…The analgesic effects of PPAR agonists may also be mediated via modulation of cellular organelles. For example, a combination drug therapy of the synthetic PPARγ agonist pioglitazone with D‐cycloserine attenuates chronic orofacial neuropathic pain and associated anxiety by improving mitochondrial function following trigeminal nerve injury (Lyons et al ., ). With the molecular mechanisms continuing to be elucidated, these findings widen the scope and increase the appeal of PPAR agonists as therapeutic agents for treating pain.…”
Section: Evidence From Pharmacological or Genetic Manipulation Studiesupporting
confidence: 74%
See 1 more Smart Citation
“…The analgesic effects of PPAR agonists may also be mediated via modulation of cellular organelles. For example, a combination drug therapy of the synthetic PPARγ agonist pioglitazone with D‐cycloserine attenuates chronic orofacial neuropathic pain and associated anxiety by improving mitochondrial function following trigeminal nerve injury (Lyons et al ., ). With the molecular mechanisms continuing to be elucidated, these findings widen the scope and increase the appeal of PPAR agonists as therapeutic agents for treating pain.…”
Section: Evidence From Pharmacological or Genetic Manipulation Studiesupporting
confidence: 74%
“…These findings also suggest that PPARγ‐mediated signalling in the lateral PAG may represent a potential therapeutic target for future development of effective therapies for treating comorbid chronic pain and stress‐related disorders such as anxiety and depression. The therapeutic potential of PPARγ for treatment of pain and mood disorder comorbidity is also supported by evidence that pioglitazone attenuates chronic constriction injury (CCI)‐induced depression‐related behaviour in the forced swim test in rats (Garg et al ., )), reduces anxiety‐like behaviour in a mouse model of chronic orofacial neuropathic pain (Lyons et al ., ) and augments both the anti‐depressant and the antinociceptive effects of fluoxetine in the rat CCI model of neuropathic pain (Murad and Ayuob, ). Additional studies on the therapeutic potential of PPAR agonists (including those for PPARα and PPARβ/δ) for treatment of the affective/emotional component of chronic pain are warranted.…”
Section: A Potential Role For Ppar Signalling In Interactions Betweenmentioning
confidence: 97%
“…As for the previously described tests, when LDB is performed in neuropathic pain models anxiety‐like behaviours can be observed 4 (Chen et al, 2013; Guimaraes et al, 2019; Matsuzawa‐Yanagida et al, 2008; Narita, Kaneko, et al, 2006; Narita, Kuzumaki, et al, 2006; Sieberg et al, 2018; Yalcin et al, 2011) to 8 weeks post‐surgery (Barthas et al, 2017; Lyons et al, 2015, 2018; Sellmeijer et al, 2018; Suzuki et al, 2007; Yalcin et al, 2011), except for the SCI model in which no decrease in time spent in light box was detected (Boadas‐Vaello et al, 2018; Table 1, Figures 2 and 3). Three studies also demonstrated a decrease in the time spent in the light box already detectable at 2 weeks after neuropathic pain induction (Chen et al, 2019; Gambeta et al, 2018; Mutso et al, 2012).…”
Section: Evaluating Anxiety‐like and Depression‐like Behaviours In Anmentioning
confidence: 99%
“…Despite the challenges faced when assessing behavioural responses in the orofacial region, due to the location and complex anatomy of the TMJ, several attempts have been made to develop direct behavioural tests. 6,7 Ren reported, for the first time in 1999, a method for assessing mechanical allodynia in the rat TMJ using a monofilament. 7 Subsequently, this method has been improved in several other studies and is currently performed by placing a rat into an individual plastic cage and measuring the response threshold using a digital device consisting of a rigid filament linked to an electronic device.…”
Section: Introductionmentioning
confidence: 99%